High-fidelity single-shot readout of single electron spin in diamond with spin-to-charge conversion - Qi Zhang (Nature Portfolio, 2021)
The NV centre in diamond has been used extensively in quantum information processing; however fault-tolerant readout of its spin remains challenging. Here, Zhang et al demonstrate a robust scheme that achieves high-fidelity readout via spin to charge conversion.